The adoption of sustainable practices in livestock production systems in tropical Andean Páramos - Carlos Julián Ramírez-Gómez; Andrés García-Cuervo; Holmes Rodriguez-Espinosa (Frontiers in Sustainable Food Systems)
The geographical areas of the Andean paramo are considered strategic and highly important ecosystems both for their ecosystem services and for being a great support for society based on what water resources imply. However, these ecosystems have been affected by livestock production, which is one of the main activities carried out in these areas. This study highlights the importance of approaching farmers who inhabit these areas from an approach of adopting sustainable technologies and practices in livestock farming so that they can contribute to the conservation of the environment. The study has two main objectives (1) to develop the concept of technology adoption in agriculture, starting from its main categories and approach variables until reaching its relationship with the adoption of sustainable and conservation practices in livestock farming, and (2) provide a conceptual basis that interrelates adoption, livestock and páramo areas as a geographic environment. Finally, this proposed framework can serve as a reference to carry out empirical analysis seeking to test various hypotheses.